Leadership In Action : Issues and Observations-Realizing the Power of Candid Conversations - Radonsky, TZiPi; Rego, Lyndon (Center for Creative Leadership, 2009)
Candid conversations are a precursor to collective action. But they require active listening and thoughtful, kind feedback.